2014
DOI: 10.1073/pnas.1409945111
|View full text |Cite
|
Sign up to set email alerts
|

Activation of transcription and retrotransposition of a novel retroelement, Steamer , in neoplastic hemocytes of the mollusk Mya arenaria

Abstract: Significance The soft shell clam in many areas of the North Atlantic is afflicted with a fatal leukemia-like disease of unknown origin. Leukemic cells from the diseased animals were found to release reverse transcriptase and to express high RNA levels of a previously unknown member of the gypsy family of retroelements, Steamer . The DNA copy number of the element was increased to enormously high levels in diseased cells, mediated by reverse transcription and integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 50 publications
2
63
0
Order By: Relevance
“…Output from BLAST querying each product from primers Stmr2988F and Stmr3340R to the nr database at NCBI returned high scoring matches only to the canonical Steamer retrotransposon sequence KF319019 (Arriagada et al 2014). Pairwise alignments from BLAST, and multiple sequence alignment (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Output from BLAST querying each product from primers Stmr2988F and Stmr3340R to the nr database at NCBI returned high scoring matches only to the canonical Steamer retrotransposon sequence KF319019 (Arriagada et al 2014). Pairwise alignments from BLAST, and multiple sequence alignment (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Examination of a variety of bivalves demonstrates that the Steamer retrotransposon, which is known to be present in high copy numbers and is highly expressed in disseminated hemic neoplasia in Mya arenaria (Arriagada et al 2014, Metzger et al 2015, is also present in the genome of other relatively phylogenetically unrelated bivalves including Ensis directus and Macoma balthica. Furthermore, that Steamer is absent from Mya truncata (closely related to, but geographically isolated from, M. arenaria), and from Siliqua patula (closely related to, but geographically isolated from, E. directus) suggests that the distribution of this retrotransposon is not due to ancient common ancestry, but rather due to more recent crossspecies horizontal transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Arriagada et al (2014) have identified and characterized a novel retrotransposon named Steamer with an expression strongly associated with DN in M. arenaria, which constitutes a new molecular marker of the disease in softshell clams.…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…This equilibrium may also be threatened by distinct sensitivity to diseases, such a leukemia. This epidemic transmissible disease is caused by the insertion of retroviral sequences in the genome of the mussels and has recently been shown to spread horizontally [35,36]. It is well known to affect many bivalves species, including Mya arenaria and Mytilus spp.…”
Section: Population Dynamicsmentioning
confidence: 99%